Midwives and Dukun Beranak, the Choices for Handling Childbirth - Nur Janti (Universitas Gadjah Mada, 2020)
Since the colonial era, there have been attempts to provide clinical childbirth services by establishing midwifery schools. Although these schools were closed, reorganized then re-opened several times, in an effort to graduate native midwives in the colony. The majority of the European doctors believed the existence of native midwives could reduce mortality rates for difficult deliveries. The colonial government also tried to replace dukun beranak (local midwives) with graduate midwives, as many doctors considered dukun beranak practices unsafe and unhygienic. Of note, even though midwifery school graduates provided childbirth services, most of the population preferred to use dukun beranak. This situation continued until independence. Dukun beranak remained the preferred provider of assistance among the working and lower class. The continued popularity of the dukun beranak can be seen as a colonial failure to replace them. After the proclamation of Indonesian independence, midwives who supported the Indonesian Republic, still provided childbearing assistance although with limited infrastructure and inadequate personnel during the independence war. Midwives also founded a midwifes association, rebuilt the national midwifery system, and discontinued colonial elements. This transformation can be interpreted as the decolonisation of midwifery. Midwives and dukun beranak were the available options for assisting in the labour of an Indonesian woman. The Indonesian government had a different approach to the colonial government toward society and dukun beranak and built cooperation between midwives and the dukun beranak. The cooperative work among midwives and dukun beranak changed awareness of Indonesian women’s reproductive health matters. This article traces efforts to provide safer childbirth services by looking at the problem through the lens of midwives and dukun beranak relations. The evolution of this relationship shows the decolonisation process inside midwifery and childbearing services.